Haemostatic, Endothelial and Lipoprotein Parameters and Blood Pressure Levels in Women with a History of Preeclampsia - He, Shu; Silveira, Angela; Hamsten, Anders; Blombäck, Margareta; Bremme, Katarina (Thrombosis and Haemostasis, 1999)
To determine whether perturbations of haemostatic function and lipoprotein metabolism prevail long after preeclampsia and increase the risk of future coronary heart disease (CHD), we conducted a follow-up study in women with (cases, n = 25) or without (controls, n = 24) a history of preeclampsia. Blood samples were taken in the follicular and in the luteal phases of a menstrual cycle. Levels of blood pressure (BP) and proteinuria measured during the index pregnancy were included in the evaluation. Compared to control women who had undergone a normal pregnancy, the formerly preeclamptic patients had higher systolic (p <0.01) and diastolic (p <0.05) BPs and increased plasma levels of von Willebrand factor (vWF), fibrinogen, cholesterol, triglycerides and very low density lipoprotein (VLDL) (all p <0.05). The lipid, vWF, and fibrinogen levels were positively related to the degree of BP elevation but not to the degree of proteinuria during the index pregnancy. Except for the increase in vWF level, all biochemical perturbations were only present in the luteal but not in the follicular phase samples. In conclusion, persistent endothelial dysfunction with ensuing dysregulation of blood pressure, haemostatic perturbation and dyslipoproteinemia after preeclampsia may indicate a proneness to future CHD.